CHALLENGES FACED BY ESL TEACHERS IN INCORPORATING TECHNOLOGY IN ESL CLASSROOMS - Tsen Mui Ling; Nur Yasmin Khairani Zakaria (INTERNATIONAL JOURNAL OF HUMANITIES, PHILOSOPHY AND LANGUAGES (IJHPL), 2025)
The integration of technology in English as a Second Language (ESL) classrooms has become increasingly essential in modern education, offering opportunities to enhance pupils’ engagement and learning outcomes. As for ESL teachers, it is important to integrate different kinds of technologies to cater different needs of pupils and to attract them towards learning a second language. However, ESL teachers face several challenges in effectively incorporating technology into their teaching practices. This paper explores the challenges encountered by ESL teachers in incorporating technology in ESL classrooms. By understanding these challenges, this paper aims to provide insights for overcoming barriers and fostering more effective and inclusive technology use in ESL education. In this research, the author employed qualitative research methodology to collect data. Semi-structured interview was conducted with five English language teachers from primary government schools to enquire about challenges in incorporating technology in ESL classrooms. Participants ought to have taught for at least five years. The teachers were being chosen using purposive sampling. The interview was transcribed and analysed thematically. The findings had shown that the challenges faced by ESL teachers in incorporating technology in ESL classrooms were such as lack of technology tools, technological barriers in terms of accessibility to the Internet and the inadequacy of the teacher’s digital competency. Pedagogical implications to overcome challenges faced by ESL teachers in incorporating technology in ESL classrooms are provided for ESL teachers and policy makers.